Emerging societies : coexistence of childhood malnutrition and obesity - Kalhan, Satish C.; Prentice, Andrew; Yajnik, Chittaranjan S. (Nestle Nutrition Institute workshop series. Pediatric program, 2009)
In many developing and emerging societies, the coexistence of malnutrition and obesity is becoming prevalent. This book presents an epidemiological overview, including regional case studies from India, China and Africa.